2011
DOI: 10.1111/j.1467-9922.2011.00670.x
|View full text |Cite|
|
Sign up to set email alerts
|

Investigating Deaf Children's Vocabulary Knowledge in British Sign Language

Abstract: This is the unspecified version of the paper.This version of the publication may differ from the final published version. Permanent repository link AbstractThis study explores different aspects of the mapping between phonological form and meaning of signs in British Sign Language (BSL) by means of four tasks designed to measure meaning recognition, form recognition, form recall, and meaning recall. This is the first time that four such tasks have been explicitly put together to measure the degrees of strength… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 41 publications
5
23
0
5
Order By: Relevance
“…The current results add to the growing literature of identifying language difficulties in children using signed language: BSL (Herman, Rowley, Mason, & Morgan, ; Marshall et al., ; Mason et al., ; Morgan, Herman, & Woll, ; Woll & Morgan, ) and ASL (Novogrodsky, Fish et al., ; Quinto‐Pozos et al., , Quinto‐Pozos, Forber‐Pratt, & Singleton, ). These findings suggest that reliable assessment tools may need to be developed for specific language backgrounds, such that nonnative signers’ scores should be compared to nonnative norms and native signers’ scores should be compared to native norms (Herman, Holmes, & Woll, ; Mann & Marshall, ). More research needs to be conducted to account for the wide variability in age at exposure to a sign language and its impact on learning.…”
Section: Discussionmentioning
confidence: 99%
“…The current results add to the growing literature of identifying language difficulties in children using signed language: BSL (Herman, Rowley, Mason, & Morgan, ; Marshall et al., ; Mason et al., ; Morgan, Herman, & Woll, ; Woll & Morgan, ) and ASL (Novogrodsky, Fish et al., ; Quinto‐Pozos et al., , Quinto‐Pozos, Forber‐Pratt, & Singleton, ). These findings suggest that reliable assessment tools may need to be developed for specific language backgrounds, such that nonnative signers’ scores should be compared to nonnative norms and native signers’ scores should be compared to native norms (Herman, Holmes, & Woll, ; Mann & Marshall, ). More research needs to be conducted to account for the wide variability in age at exposure to a sign language and its impact on learning.…”
Section: Discussionmentioning
confidence: 99%
“…Next, we tested the construct validity of the items based on the order of difficulty, predicted by the model of strength of form-meaning mapping (see Table 1). Findings from previous research on the BSL version of the test had confirmed the validity of the model (Mann & Marshall, 2012). However, because the target populations differed and test adaptations carried out (see above), it is important to investigate the construct validity of the ASL version.…”
Section: Validitymentioning
confidence: 94%
“…A signer, who can recall the meaning (level 4) or form (level 3) of a sign, is also likely to recognize that sign's form (level 2) or meaning (level 1) when presented. Evidence in support of the construct includes research on signed (Mann & Marshall, 2012, Mann, Roy, & Marshall, 2013 and spoken language Laufer & Godlstein, 2004), which revealed significant differences in participants' performance across tasks. With each of the four mappings representing a different level of vocabulary strength, the test provides an estimate of test takers' vocabulary knowledge.…”
Section: The Web-based Bsl Vocabulary Test (Bsl-vt)mentioning
confidence: 98%
See 1 more Smart Citation
“…Hart and Risley (1995) found that children of mothers who spoke more frequently to their children had larger receptive and expressive vocabularies than children of mothers who spoke less frequently to their children. Whether due to the quantity of mothers’ speech, limited access to linguistic activities (Hoff and Tian 2005), or deafness (Mann and Marshall forthcoming), limited language experience might result in persisting weakness in phonological representations.…”
Section: Receptive-expressive Gap In Bilingualsmentioning
confidence: 99%